ASSESSMENT RESULTS OF COLLECTION SAMPLES OF WINTER WHEAT ON TOLERANCE TO SMUT (TILLETIA LEVIS) - N. V. Shishkin; T. G. Derova; D. M. Marchenko (Зерновое хозяйство России)
The article gives the analysis of the experiments of 106 winter wheat cultivars of different origin on tolerance to smut fungi.  The pathogen being present from the moment of sprouting till seed maturation makes a suppressing effect on the plant. It reduces seed germination, makes plants be stunted and reduces seed filling. Besides grain infected by smut is unusable for food and forage. To protect wheat seeds from smut pathogen we widely apply chemicals, but a more ecological and less expensive method is of great importance nowadays. It’s a technology of hybridization and cultivation of tolerant to the disease cultivars, for selection of which we need the sources of resistance and tolerance to the pathogen.  At the experimental field artificially infected with smut of Rostov origin the cultivars ‘Zolotokolosa’, ‘Pivna’ (Ukraine), ‘Hoff’, ‘KS 93 U76’ (US), Elba (Latvia) showed the best tolerance to smut. The infection of the cultivars varied from 0 till 9,8% during different years. Thirteen cultivars showed little response to the pathogen (from 10,7 till 22,6%). 49 cultivars showed average response to the pathogen, it’s 46,2% of all studied cultivars. 39 cultivars showed the highest response to the pathogen, that is 36,8% of all cultivars. The chosen cultivars are the most valuable material for further selection on smut tolerance.